IMPLEMENTASI MANAJEMEN PESERTA DIDIK DI SDN DEMANGAN 1 BANGKALAN - Andika Adinanda Siswoyo; Ajib Akhmad Fadhoni, Endang Sulistianingsih, Frissenda Septrianur Marinda Karno Putri (CV. ADIBA AISHA AMIRA, 2025)
This research aims to analyze the implementation of student management at SDN Demangan 1 Bangkalan. A qualitative descriptive method with a tendency for analysis was used. The research subjects were students and teachers of SDN Demangan 1 Bangkalan. The data collection techniques used were observation, interviews, and documentation. The research results showed that the management at SDN Demangan 1 is very good. This school is the only elementary school in East Java, especially in Bangkalan, that has an athlete class program. In addition, recently, SDN Demangan 1 has also been running a literacy program for students who are less literate